ANALISIS KOHESIVITAS KELOMPOK DAN BUDAYA ORGANISASI TERHADAP WORK ENGAGEMENT PADA PEKERJA GENERASI MILENIAL DI WILAYAH KABUPATEN SLEMAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Muhammad Rizqi Saifuddiin; Kusuma Chandra Kirana; Gendro Wiyono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to examine and analyze group cohesiveness, organizational culture,job satisfaction and work engagement on millennial generation workers in the SlemanRegency area. The main problem in this research is work engagement. The researchdata was collected by distributing questionnaires through google forms and distributedto 80 respondents spread across the Sleman Regency. The research method used inthis study is a quantitative research method, then the research data collectiontechnique is purposive random sampling and uses data analysis tools SPSS (Statistic Package for Social Science), Partial Least Square (PLS). Based on the results, thefactors that influence work engagement are organizational culture and jobsatisfaction. The evidenced by the results of hypothesis testing which show P Values <0.05 which is 0.000 and P Values < 0.05 which is 0.032 while the group cohesivenessvariable has no effect on work engagement in millennial generation workers in theSleman Regency area